MOTIVASI BELAJAR PESERTA DIDIK KELAS VIII PADA MATA PELAJARAN IPS DI SMPN 6 PONTIANAK - Rika Juwarti; Aminuyati Aminuyati; Husni Syahrudin (Universitas Tanjungpura, 2020)
AbstractThe study aims to explain and analyze intrinsic and extrinsic motivation in the form of desires and desires to succeed, encouragement and needs in learning, hopes and ideals, appreciation, conducive learning environment and interesting learning activities for students of class VIII E in social studies subjects at SMP Negeri 6 Pontianak. This research uses a qualitative methods. The results showed that (1) The desire and success of the participants did not do the assignments given by the studentsseriously. (2) The encouragement and the needs of the studenst’ learning teachers could be said to be poor, the students who looked lack of focus and look bored. (3) Expetations and ideals of participants can be quite good, but do not have a major impact in influencing students’desire to be more active in learning social studies subjects. (4) Awards in learning given by teachers to students can be is said to be good enough in fostering learning impiulse in student. (5) Learning environment can be said to be unfavorable, students feel overheating due to be inadequate classroom facilities (6) Learning activities can be said to be inadequate, students often feel bored in social studies learning because the methods used by teacher are less varied. Keywords: Learning Motivations, Students.